Environmental Contaminants Using natural archives to track sources and long-term trends of pollution - Blais, Jules M.; Rosen, Michael R.; Smol, John P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
The human footprint on the global environment now touches every corner of the world. This book explores the myriad ways that environmental archives can be used to study the distribution and long-term trajectories of chemical contaminants. The volume first focuses on reviews that examine the integrity of the historic record, including factors related to hydrology, post-depositional diffusion, and mixing processes. This is followed by a series of chapters dealing with the diverse archives and methodologies available for long-term studies of environmental pollution, such as the use of sediments, ice cores, sclerochronology, and museum specimens.
1. Using natural archives to track sources and long-term trends of pollution -- 2. The influence of hydrology on lacustrine sediment contaminant records -- 3. The stability of metal profiles in freshwater and marine sediments -- 4. Calculating rates and dates and interpreting contaminant profiles in biomixed sediments -- 5. Contaminants in marine sedimentary deposits from coal fly ash during the Latest Permian Extinction -- 6. Lake sediment records of preindustrial metal pollution.  Colin Cooke and Richard Bindler --  7. Lacustrine archives of metals from mining and other industrial activities -- 8.  Organic pollutants in sediment core archives -- 9. Environmental archives of contaminant particles -- 10. Long range atmospheric transport in Arctic regions using lake sediments -- 11. Tracking long-range atmospheric transport of trace metals, polycyclic aromatic hydrocarbons, and organohalogen compounds using lake sediments of mountain regions -- 12. Tracking contaminant transport from biovectors -- 13. Using peat records as natural archives of past atmospheric metal deposition -- 14. Historical contaminant records from sclerochronological archives -- 15. Contaminant records in ice cores -- 16. Use of catalogued long-term biological collections and samples for determining changes in contaminant exposure to organisms.-Chapter 17. Using natural archives to track sources and long-term trends of pollution: Some final thoughts and suggestions for future directions.
Keywords: Water pollution; Water quality; Environmental management; Hydrology; Environmental chemistry; Ecotoxicology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Water Policy/Water Governance/Water Management; Hydrology/Water Resources; Environmental Chemistry; Ecotoxicology